2019
DOI: 10.1155/2019/9893615
|View full text |Cite
|
Sign up to set email alerts
|

Critical Literature Review into Planning of Inter-Terminal Transport: In Port Areas and the Hinterland

Abstract: Nowadays, the major ports around the world usually consist of multiple terminals and service centers which are often run by different operators. Meanwhile, inland terminals have been also developed to reduce port congestion and improve transport efficiency. The integrated planning of inter-terminal transport (ITT) between the seaport and inland terminals helps in providing frequent and profitable services, but also could lead to higher overall planning complexity. Moreover, the ITT system usually involves mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Furthermore, research underscores the strategic imperative of modernizing intermodal terminals to align with overarching logistics goals (Hu et al, 2019). The literature advocates for the creation of agile, responsive, and technologically advanced logistics ecosystems, equipped to navigate the complexities of contemporary supply chain dynamics (Chowdhary, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, research underscores the strategic imperative of modernizing intermodal terminals to align with overarching logistics goals (Hu et al, 2019). The literature advocates for the creation of agile, responsive, and technologically advanced logistics ecosystems, equipped to navigate the complexities of contemporary supply chain dynamics (Chowdhary, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The growth in freight volumes greatly impacts intermodal logistics areas, such as ports and business parks in the hinterland. In this context, several ports such as Shanghai and Rotterdam are investing in multi-terminal systems, which inherently result in highly complex transport systems within the port (Hu et al 2019). As a result, companies face new challenges in the field of ITT problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the design of efficient ITT operations in the future will pose a considerable challenge for many large seaports. Hu et al [ 2 ] conducted a comprehensive literature review related to the planning of interterminal transport in port areas and the hinterland. The research was motivated by two factors: the limited research related to the integrated planning of ITT between seaport and inland terminals and the limited studies that summarized the research findings and identified the directions for future research regarding ITT.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To provide acceptable service levels for importers and exporters, these infrastructural facilities and services need to be addressed and considered by port authority. Hu et al [ 2 ] stated that a multiterminal system increases the complexity of the container transport process. Figure 1 illustrates the process of unloading and loading containers from/to a ship at a typical modern container terminal.…”
Section: Introductionmentioning
confidence: 99%